Problematika Penerapan Kurikulum Merdeka Dalam Mata Pelajaran Pai di SMA N 1 Mojotengah - Yuliana Yuliana; Rifqi Muntaqo; Nur Farida (STIKes Ibnu Sina Ajibarang, 2024)
The aims of this research are: 1) To determine the implementation of the independent curriculum in Islamic Religious Education courses at SMA N 1 Mojotengah Wonosobo. 2) To find out the problems of implementing an independent curriculum in learning Islamic Religious Education at SMA N 1 Mojotengah Wonosobo. 3) To determine efforts to overcome the problems of implementing the independent curriculum in Islamic Religious Education subjects at SMA N 1 Mojotengah Wonosobo.This research is qualitative research where the research is descriptive qualitative type. The method used in this research uses research methods. With the research subjects being the school principal, deputy head of curriculum, Islamic Religious Education subject teachers, female students in class X and class XI. In this research, data collection techniques used observation, interviews and documentation. To analyze the data the author uses data reduction, data presentation and conclusions.The results of the author's research conducted in the field show that, 1) The implementation of the independent curriculum in Islamic Religious Education subjects at SMA N 1 Mojotengah Wonosobo goes through several stages of activities, namely preparation of PAI teachers in implementing the Independent curriculum, implementation of Independent curriculum learning, assessment of Independent curriculum learning . 2) Problems in implementing the Merdeka curriculum in PAI subjects at SMA N 1 Mojotengah Wonosobo include a lack of training, less than optimal differentiated learning, and a mindset that has not changed. 3) Efforts to Overcome the Problems of Implementing the Independent Curriculum in PAI Learning at SMA N 1 Mojotengah Wonosobo include attending workshops, increasing teacher creativity, sharing to change the mindset in teaching.